LAZ DASI'S Education and Literacy Program in Increasing the Awareness of The People of Central lombok to Pay Zakat through LAZ DASI - Siti Rahmawati RHM; Agus Mahmud; Nurul Susianti; Hariono Hariono (UIN Mataram, 2023)
This research is motivated by the data source of BPS Central Lombok Regency, the number of Muslim residents who are said to be economically capable and have income shows that the number of Central Lombok Muslim residents who are able to pay zakat with the number of residents or people who pay zakat through LAZ DASI and BAZNAS Central Lombok is said to be insignificant. This may occur because public awareness of zakat can be influenced by a person's knowledge or understanding of zakat itself. So based on this data, people who still lack awareness of paying zakat need educational and literacy activities among the community carried out by institutions or zakat management bodies such as LAZ DASI to provide understanding and knowledge about the program for awareness in paying zakat through official zakat management institutions. This type of research is descriptive qualitative research. The data collection methods used are observation, interview and documentation methods. While the data sources used are primary data sources and secondary data. The results of the research conducted by researchers show that education and literacy carried out by LAZ DASI Central Lombok have significantly increased public awareness to pay zakat at LAZ DASI Central Lombok. Educational activities carried out are through partner meetings, socialization, volunteer communities, and zakat awareness safaris. While literacy activities are carried out through the reading bale ceria lombok and LAZ DASI magazine.